Seniman Thalib R. Eka: Kajian Biografi Kreatif dan Eksistensi Hasil-Hasil Karya Seninya - Ine sintiya Sanuhung; I Wayan Sudana; Hasmah (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Biographical studies of artists and their artworks are important for elevating the artist's reputation and completing art historical documents, but not all artists' biographies and works have been studied comprehensively, including Thalib R. Eka as a Gorontalo artist. This study aims to reveal the creative biography of artist Thalib R. Eka and the existence of his artworks, including the factors that influence them. Employing a qualitative method with a historical approach in the biography unit, data was collected through document review, interviews, observations, and literature studies. Data were analyzed through data reduction, data presentation, and drawing conclusions. The results show that Thalib R.Eka's biography from childhood to becoming an artist was influenced by internal and external factors. Internal factors include personal interests, expertise, and developing knowledge. External supporting factors: government, artist community, gallery, curator, and mass media. The existence of Thalib R. Eka's artworks can be categorized into three: 1) paintings of various aesthetic and meaningful styles; 2) drawings with the theme of traditional Gorontalo houses with historical value; 3) reliefs with a nature theme as garden decorations. In conclusion, an artist's career is not only determined by personal interests and expertise, but is also supported by various external factors, in order to produce quality works that are worthy of appreciation.